Fedora 8 and Red Hat Enterprise Linux bible - Negus, Christopher (Wiley Pub., 2008)
Explains the features of Fedora 8 and Enterprise Linux, offering instructions on its installation, desktop interface, network and server set-up, and key system administration skills.